Effect Of Horizontal Pattern On Masonry Prism Strengthened Using Carbon Reinforced Polymer (Cfrp) And Glass Reinforced Polymer (Gfrp) - Mohd Ruzi, Nor Aerina Aerin (Universiti Sains Malaysia, 2018)
Brick construction is widely uses in all parts of the world over the last century especially wall construction. The use of these materials is closely related to several factors, among which are easily obtained, cheap and easy job control. However, there are some disadvantages arise in the application of brick construction which brick wall will eventually crack wherever exceed the load capacity of the brick. Therefore, the study is focus on the strengthening method on wall construction without changing the construction materials. In this study, strengthening method using fibre reinforced polymer method is selected in order to observe the maximum load capacity and compare behaviour against the loading that can be obtained when strengthen by fibre reinforced polymer. Characterization tests such as absorption test and compressive strength test were conducted on concrete masonry unit (CMU) to determine its characteristics before mortar mix were used as a binder for the specimens. Compression and flexural tests were conducted to characterize the mortar mix used. A total of 12 prisms specimens with four different conditions were produced for the compressive strength test. Those prism specimens are classified as strengthened with CFRP in horizontal orientation (A), strengthened with GFRP in horizontal orientation (B), control specimen without fibre polymer (C). Each condition has a total of three specimens each to compare their outcomes. The results of observations and tests found the average value of the failure load is as follows (A) 148 kN, (B) 186 kN and (C) 180 kN. The conclusion that can be made is strength (B) which specimen strengthened with GFRP in horizontal pattern is the highest compare (C) and (A) which prove it can increase the load capacity of structure and crack pattern could be controlled.